PENGEMBANGAN MULTIMEDIA PADA PEMBELAJARAN LAS GAS METAL ARC WELDING DI SMKN NEGERI 2 SUNGAILIAT KABUPATEN BANGKA - Arief Amirudin; Soemedi Hadiyanto (JURNAL PENDIDIKAN ROKANIA, 2021)
Online learning is hampered by the improvement of skill competencies due to the limitations of student -teacher interaction, so multimedia development innovation is needed. The purpose is to study the effectiveness of multimedia development of power point -based android applications on GMAW welding learning. Method; development refers to the ADDIE model. Quantitatively descriptive data collection in March 2021 on 33 students and done purposively. Measuring tool list of expert assessments and observations, data processing with SPSS for windows and test The posttest-only control group design. Results; material expert validation with an average of 4.50 is very good, and media with an average of 4.36 is very good. The multimedia developed meets the requirements and is suitable for use as a learning media. The results of t-test using paired t-test obtained sig value. (2-tailed) = 0.000 <0.05 so it is concluded that both groups have unequal performance. The average of the experimental class was 69.74 and the control class was 61.63. MPI can be used in learning activities and improve student learning achievement.